Activation of organic reactions by perchlorates - Deshpande, Suvarna S.; Kumar, Anil (Advances in Organic Synthesis, 2005)
Perchlorates have been frequently employed to promote a variety of synthetic transformations under ambient conditions. For example, the LiClO4-diethyl ether solvent medium has proven to be a powerful substitute for external high pressure for Diels-Alder reactions and other organic reactions. In this chapter are discussed several such organic transformations where perchlorates have played highly significant role in promoting their rates and yields.

Catalyzing Henry reactions in chloroaluminate ionic liquids - Kumar, Anil; Pawar, Sanjay S. (Journal of Molecular Catalysis A - Chemical, 2005)
Henry reactions can be accelerated in chloroaluminate room temperature ionic liquids. The choloroaluminates with higher compositions of organic species of the chloroaluminates prove to be more efficient rate promoters than the ones with lower organic species in catalyzing Henry reactions. involving both aliphatic and aromatic carbonyl compounds. The ionic liquids can be recycled five times to offer good yields. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: chloroaluminates; Henry reactions; ionic liquids; Recycling

Comment on ``Prediction of viscosity of mixed electrolyte solutions based on the Eyring's absolute rate theory and the equations of Patwardhan and Kumar by Y.-F. Hu'' (Chemical Engineering Science 2003,59,2457-2464) - Kumar, Anil (Chemical Engineering Science, 2005)

Design, syntheses, and characterization of new thermoplastic polyureas based on 3,4-ethylenedioxythiophene - Ojha, U. P.; Ramesh, C.; Kumar, Anil (Journal of Polymer Science Part A-Polymer Chemistry, 2005)
New thermoplastic polyureas labeled PUn (n = 2, 3, 4, 6, 7, 9, or 10), based on 3,4-ethylenedioxythiophene (EDOT) with flexible aliphatic spacers, were synthesized and characterized for the first time. EDOT was chosen as a replacement for the aromatic phenyl group in conventional thermoplastics based on urea linkages to improve solubility without compromising the thermal properties. As synthesized, all the samples exhibited a semicrystalline nature. The glass-transition and melting temperatures showed a strong dependence on the spacer length. A comparison of the thermal properties of these polyureas with the corresponding phenyl analogues indicated that EDOT was a viable heteroatomic analogue of the phenyl group to be inserted into the main-chain polyureas without hampering their thermal stability. The polyureas with spacer lengths greater than hexamethylene formed transparent gels in N-methylpyrrolidone, 1,1,2,2-tetrachloroethane, and dimethyl sulfoxide. The molecular packing of the polyureas was assigned with wide-angle X-ray diffraction studies. (c) 2005 Wiley Periodicals, Inc.
Keywords: 3; 4-ethylenedioxythiophene; heteroaromatic polymers; Polyurea; polyurea gels; Thermogravimetric analysis (TGA); thermoplastics; WAXS

Effect of connectivity and terminal functionality on mesophase behaviour of thermotropic liquid crystals containing biphenyl units - Ranganathan, T.; Ramesh, C.; Kumar, Anil (Liquid Crystals, 2005)
A series of 4,4'-disubstituted biphenyls, designated as series HBC, in which, one substituent is an ester group linked directly to the ring and the other is the hydroxy-containing group O(CH2)(n)OH, have been prepared and analysed by differential scanning Calorimetry, polarizing optical microscopy and X-ray diffraction. The introduction of a trimethylene unit between the ester functional group and the biphenyl moiety of the HBC series gives rise to the HBB series, which did not exhibit liquid crystalline behaviour. Interestingly, mesophase behaviour could be restored by replacing the methylene group ( of the trimethylene unit) that was directly attached to the biphenyl ring by a keto group (HBOB series). When the terminal hydroxy group of these three series was substituted by a group such as acetoxy or hydrogen, the transition temperatures were reduced, and the disappearance of mesophase behaviour was observed in some cases. However, this could be recovered by the replacement of the ester group by a carboxylic acid group.

Effect of NaBr, KCl, KBr, and MgCl2 on viscosities of aqueous glycine and L-alanine solutions at 298.15 K - Badarayani, Rohini; Satpute, D. B.; Kumar, Anil (Journal of Chemical and Engineering Data, 2005)
Viscosities, η, of glycine and L-alanine are measured in aqueous solutions of NaBr, KCl, KBr, and MgCl2 up to high concentrations at 298.15 K. This study suggests that 1:1 electrolytes enhance the structure making ability of the amino acids whereas MgCl2 does not. The viscosities of the above solutions are correlated using a simple model with two interaction parameters.

Main chain thermotropic liquid crystalline polyurethanes containing biphenyl mesogens based on novel AB-type self-polycondensation route: FT-IR and XRD studies - Ranganathan, T.; Gowd, E. B.; Ramesh, C.; Kumar, Anil (Journal of Polymer Science Part A-Polymer Chemistry, 2005)
The detailed mesophasic characterization of main chain liquid crystalline polyurethanes containing biphenyl mesogen, which were synthesized by the novel AB-type self-polycondensation approach, was carried out by using Differential Scanning Calorimetry (DSC), Polarized Optical Microscopy (POM), variable temperature X-ray Diffraction (XRD), and Fourier Transform Infrared (FT-IR) spectroscopic studies. The type of mesophase present in these polymers was identified to be the smectic A phase by POM and XRD studies. The smectic layer thickness was found to increase as the length of the spacer increased. The effect of temperature on the hydrogen bonding was analyzed by FT-IR studies. The curve-fitting analysis of the NH stretching and C=O stretching modes of vibrations indicated a gradual decrease in hydrogen bonding during the transition from the crystalline state to the mesophase. The mesophase to isotropic liquid transition was then accompanied by the complete disappearance of the hydrogen bonding. The biphenyl bands also showed changes during phase transitions due to the coupling of biphenyl vibration modes with the urethane linkage attached to it. (c) 2005 Wiley Periodicals, Inc.
Keywords: FT-IR; liquid-crystalline polymers; polyurethanes; XRD studies

Pressure dependence of the dissociation of acetic, benzoic, mandelic and succinic acids at 298.15 K - Kumar, Anil (Thermochimica Acta, 2005)
Dissociation constants for acetic, benzoic, mandelic and succinic acids have been measured at 298.15 K as a function of pressure up to 138.8 MPa. The spectrophotometric technique using Bromocresol Green as the optical indicator was employed up to ionic strength of 0.03 mol kg(-1) in aqueous solution. Thermodynamic dissociation constants were calculated with the Davies activity coefficient equation. The pressure dependences of the ionization constants for the weak acids can be described by the equation of Lown, Thirsk and Wynne-Jones, application of which leads to accurate partial molal volume change on ionization, Delta(V) over bar (o) and compressibility change, Delta(K) over bar (o) at 0.1 MPa. (C) 2005 Elsevier B.V. All rights reserved.
Keywords: Acetic acid; benzoic acid; dissociation constants; high pressure; mandelic acid; succinic acid

Reassessment of the binary, ternary, and quaternary interactions in mixed electrolytes from thermodynamic quantities: the systems with uncommon ions containing hydrophobic character - Kumar, Anil (Journal of Physical Chemistry B, 2005)
Accurate estimates of the binary, ternary, and quaternary interactions in aqueous ionic mixtures with uncommon ions with hydrophobic character are presented. For this purpose, the values of the excess Gibbs free energy of mixing, Delta(m)G(E), obtained from our earlier isopiestic osmotic coefficients (Kumar, A. J. Phys. Chem. B 2003. 107, 2808) for the mixtures of NaCl with four guanidinium (Gn(+)) salts-CH(3)COOGn, GnNO(3), GnClO(4), and Gn(2)SO(4) are analyzed with the help of the method developed by Leifer and Wigent. The methodology of Leifer and Wigent is based on the equations of Scatchard-Rush-Johnson and Friedman's cluster integral expansion theory. The Scatchard-Rush-Johnson theory explicitly considers the quaternary and higher-order ionic interactions in the mixtures as compared to the specific ion interaction theory of Pitzer, which accounts for binary and ternary interactions only. The contributions due to binary, ternary, and quaternary interaction terms to total Delta(m)G(E) are estimated and discussed critically. Also, the interaction between the same two cations, for example, Gn(+)-Gn(+), is estimated and found significant, which otherwise cannot be obtained by the use of Pitzer's theory. The information obtained from the analysis of Delta(m)G(E) is also supported by the newly measured excess volumes of mixing, Delta(m)V(E), at 298.15 K. The individual contributions of the binary, ternary, and quaternary interaction terms to total Delta(m)V(E) are described. The binary, ternary, and quaternary interaction terms for both Delta(m)G(E) and Delta(m)V(E) are analyzed in terms of Friedman's cluster integral expansion theory.

Recent applications of chloroaluminate ionic liquids in promoting organic reactions - Kumar, Anil; Sarma, Diganta (Symposium on Ionic Liquids - Fundamentals, Progress, Challenges and Opportunities held at the 226th American-Chemical-Society National Meeting, 2005)
Chloroaluminate ionic liquids composed of AICl(3) and organic cations can promote a variety of organic reactions. The composition of these chloroaluminate ionic liquids governs the acidity and basicity of solvent media, in which the reactions are carried out. Useful physico-chemical properties of these ionic liquids and the recent work on their role in accelerating organic reactions are described in the present article.

Stereoselectivity ratios in a simple Diels-Alder reaction in aqueous salt solutions of alcohols - Deshpande, Suvarna S.; Kumar, Anil (Tetrahedron, 2005)
This is the first exhaustive report on the variation of stereoselectivity ratios for a simple Diels-Alder reaction between cyclopentadiene and methyl acrylate. The reaction was carried out in aqueous mixtures of methanol, ethanol, propan-1-ol and butan-1-ol in presence of LiClO4, LiCl, NaCl, KCl, CaCl2 and MgCl2. The endo sterecisomer decreases with the increase in carbon chain length of the alcohol. However, LiClO4, a salting-in agent in water becomes salting-out in aqueous mixtures of alcohols. The solvent properties, thus can be attuned by adjusting the amount of solvents and salts. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: aqueous alcohols; Diels-Alder reaction; endolexo ratios; salts

Wet-chemical templateless assembly of metal nanowires from nanoparticles - Maddanimath, Trupti; Kumar, Anil; D'Arcy-Galla, J.; Ganesan, P. G.; Vijayamohanan, K.; Ramanath, G. (Chemical Communications, 2005)
We describe a new, simple, room-temperature wet-chemical approach for assembling Au and Ag nanoparticles into nanowire networks, without the use of lithographic templates. Five to 35 nm-diameter nanowires passivated with a thin organic layer were synthesized by mechanically agitating a biphasic liquid mixture of an aqueous hydrosol containing the nanoparticles, and toluene. Nanowire structure and surface chemistry are discussed based on electron microscopy, UV-visible spectroscopy and thermogravimetric analyses.

Comparison of flow structures in spacer-filled flat and annular channels - Ranade, Vivek V.; Kumar, Anil (Desalination, 2006)
Spacers are designed to create directional changes in the flow through membrane modules. Such secondary flow structures reduce concentration polarization and membrane fouling. Obviously, type of the spacer used in membrane modules strongly influences the resulting flow and therefore performance of the module. In this work, we have modeled detailed fluid dynamics of spacer filled channels by using the `unit cell' approach. The validated computational fluid dynamics (CFD) model was used to evaluate performance of certain spacer shapes and compare the resulting fluid dynamics in flat and curved channels. The simulations show that fluid flow behavior in a spacer-filled flat and a spiral channel was not significantly different. This means that pressure drops and mass transfer coefficients measured in flat channels may provide adequate guidelines, which would also be valid for spiral-wound modules. The results presented in this work will have significant implications for identifying improved spacers with higher propensities to reduce fouling in membrane modules.
Keywords: annular channel; CFD; flat channel; membrane spacers

Hydrophobic effects are dominant over secondary orbital interactions for a simple Diels-Alder reaction in salt solutions - Sarma, D.; Kumar, Anil (Organic Letters, 2006)
The stereoselectivity ratios for a Diels-Alder reaction between cyclopentadiene with methyl trans-crotonate carried out in salt solutions demonstrate the dominance of hydrophobic effects over secondary orbital interactions.

Hydrophobic effects in a simple Diels-Alder reaction in water - Sarma, D.; Pawar, S. S.; Deshpande, Suvarna S.; Kumar, Anil (Tetrahedron Letters, 2006)
The endolexo ratio for a simple Diels-Alder reaction carried out in water has been used to argue that hydrophobic effects can dominate the geometries of the transition states. (c) 2006 Elsevier Ltd. All rights reserved.

Micellar behavior of dodecyldimethylethyl ammonium bromide and dodecyltrimethyl ammonium chloride in aqueous media in the presence of diclofenac sodium - Mehta, S. K.; Bhasin, K. K.; Kumar, Anil; Dham, S. (Colloids and Surfaces A-Physicochemical and Engineering Aspects, 2006)
The micellar properties of cationic surfactants (S) viz. dodecyldimethylethyl ammonium bromide (DDAB) and dodecyltrimethylammonium chloride (DTAC) in aqueous media in the presence of diclofenac sodium (D) have been investigated by spectroscopic and conductivity measurements. The UV-vis and H-1 NMR studies suggest possible packing of diclofenac sodiurn molecules in the micelles. The conductivity studies were carried out over the temperature range 288.15-308.15 K. The critical micelle concentration (cmc) and degree of counterion binding (beta) of the micelles were determined at different temperatures. Delay in micellisation was observed for both DDAB and DTAC. Thermodynamic parameters (Delta G(m)(0) Delta H-m(0) and Delta S-m(0).) for the micelle system were estimated by applying the charged pseudo-phase separation model. The results of the ternary S/D/W system were analysed in comparison with the reported results of binary SAV system. The Delta G(m)(0) values for the ternary S/D/W system in both the cases show an increase in comparison to the respective binary SAV system. However, Delta S-m(0) decreased with temperature and remained positive in both the systems. At lower temperatures, the micellisation was found to be entropy-driven while at higher temperatures it was enthalpy-dfiven. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: diclofenac sodium; dodecyldimethylethylammonium bromide; dodecyltrimethylammoniurn chloride; Electrical conductivity; spectroscopic measurements

Homogeneous nucleation temperatures in aqueous mixed salt solutions - Kumar, Anil (Journal of Physical Chemistry B, 2007)
This is the first report on the measurement of homogeneous nucleation temperature, T-H, in the presence of aqueous mixed salt systems of varying compositions and ionic strengths. The T-H,T-m (T-H value in aqueous mixed salt system) data for these systems have been analyzed in terms of a simple empirical equation. The T-H.m. values in simple aqueous mixed salts like NaCl-KCl can be approximated by linear summation of the products of ionic strength fraction and the T-H values of pure salt solutions at the same ionic strength as that of the mixture. The empirical parameter, q(0), indicating ionic interaction is related to the viscosity B-coefficients. The T-H.m data, though correlated on the basis of the B-coefficients also depends upon the mixing of two ions of like charges. Further, a linear correlation exists between the q(0) parameter and self-diffusion coefficient, D-0, of the ionic solute. The q(0) parameter is also well correlated with the rotational correlation time, T-c(h)/T-c(0) of the ionic species involved in the mixtures. It is possible to compute T-H,T-m for the salt mixtures with no common ions from the knowledge of the T-H,T-m values of the salt mixtures with common ions.

Ionic liquids as powerful solvent media for improving catalytic performance of silyl borate catalyst to promote Diels-Alder reactions - Kumar, Anil; Pawar, Sanjay S. (Journal of Organic Chemistry, 2007)
[GRAPHICS] Use of the acidic chloroaluminate ionic liquid, including the recycled ones, can improve the catalytic activity of the toluene-coordinated silyl borate in enhancing rates, stereoselectivities, and yields of Diels-Alder reactions.

Isopiestic osmotic coefficients of tetra-n-methylammonium chloride with guanidinium salts at 298.15 k - Kumar, Anil (Journal of Solution Chemistry, 2007)
Isopiestic osmotic coefficients are presented for aqueous mixtures of tetra-n-methylammonium chloride, (CH3)(4)NCl, with guanidinium salts such as GnCl, CH(3)COOGn, GnNO(3), GnClO(4) and Gn(2)SO(4) at 298.15 K up to an ionic strength of 2 mol center dot kg(-1). The osmotic coefficients are analyzed in terms of the Scatchard-Rush-Johnson equations. The activity coefficients of each electrolyte in the mixtures were calculated and fitted by the Harned-type equations. The molar excess Gibbs energy of mixing, Delta(m) G(E), of the mixtures were analyzed with Friedman's equations.
Keywords: aqueous solutions; isopiestic method; Osmotic coefficients; Scatchard-Rush-Johnson equations; tetramethylammonium salts

Insight into the micellization of dodecyldimethylethylammonium bromide (DDAB) in the presence of bovine serum albumin (BSA) - Mehta, S. K.; Bhawna; Bhasin, K. K.; Kumar, Anil (Journal of Colloid and Interface Science, 2008)
in this work, we report the effect of concentration of bovine serum albumin (BSA) on the micellization of a cationic surfactant, doclecyldimethylethylammonium bromide (DDAB). Several samples covering a wide range of concentrations of protein and surfactant have been investigated. The interactions between the moieties are investigated by measuring fluorescence quenching of BSA molecules. The aggregation number of DDAB micelles is found to be small in the presence of BSA. The formation of DDAB-BSA complex is confirmed by FTIR. Absorbance spectroscopy indicates that at higher concentration, the conformational stability of BSA in DDAB is higher. The viscosity data for protein-surfactant systems confirm conformational changes in protein chains induced by the surfactant. The cmc values for DDAB increase with increasing concentration of BSA. At higher temperatures the micellization-complexation becomes enthalpy-dominated. (c) 2008 Elsevier Inc. All rights reserved.
Keywords: Aggregation number; BSA; conductivity; conformational stability; DDAB; FFIR; fluorescence; UV-visible; viscosity

Intramolecular Diels-Alder reaction in ionic liquids: effect of ion-specific solvent friction - Tiwari, Shraeddha; Khupse, Nageshwar D.; Kumar, Anil (Journal of Organic Chemistry, 2008)
The present work aims at understanding the role of viscosity or solvent friction in ionic liquids for an intramolecular Diels-Alder (IMDA) reaction of (E)-1-phenyl-4-[2-(3-methyl-2-butenyloxy)benzylidene]-5-pyrazolone (1). The results have been analyzed on the basis of the current theoretical models, and their failure to account for the observed trends is discussed in terms of ``effective'' viscosity or microviscosity. The rates of the reaction decrease with the increasing viscosity of the ionic liquids. As evident from the anionic effect, the solute-solvent specific interactions play a role in governing the kinetics of the reaction. The lower viscosities of the bistrifluoromethanesulfonimide [NTf(2)](-) based ionic liquids as compared to those based on tetrafluoroborate [BF(4)](-) anion fail to result in a corresponding acceleration in the rates of the reaction. These contradictory results indicate that solvent microviscosity, rather than the bulk macroscopic viscosity, should be the criteria for selecting the ionic liquids as reaction media.

Ionic interactions in aqueous mixtures of hydrophilic and -phobic ions - Kumar, Anil (Pure and Applied Chemistry, 2008)
Ions of both hydrophilic and -phobic nature play a pivotal role in biological systems and during synthesis of many organic molecules. However, the interaction of a hydrophilic ion with a hydrophobic one is not a simple physical process and is useful in understanding the rate enhancement in organic transformations and thermal stability of DNA and RNA. During the talk, an attempt was made to present some of the experimental work on aqueous mixtures of these ions carried out at National Chemical Laboratory, Pune, and give a theoretical interpretation of the binary, ternary, and quaternary interactions operating in these systems. The contribution of these interaction terms to the excess free energy of mixing, Delta(m)G(E), will be analyzed.
Keywords: aqueous solutions; excess free energy; hydrophobic ions; ionic solutions; mixing effects

Ionic liquids: physico-chemical, solvent properties and their applications in chemical processes - Singh, Geetanjali; Kumar, Anil (Indian Journal of Chemistry Section A-Inorganic Bio-Inorganic Physical Theoretical & Analytical Chemistry, 2008)
A new class of compounds, called as ionic liquids, has recently emerged as potential substitute for volatile organic solvents. Ionic liquids possess certain special physico-chemical characteristics that render them very useful in different areas of research and development. In this review, the physico-chemical properties and the applications of ionic liquids in chemical processes are critically discussed and recommendations made for probing further the poorly understood aspect of this newly emerging class of compounds.

Rare earth metal triflates promoted diels-alder reactions in ionic liquids - Sarma, Diganta; Kumar, Anil (Applied Catalysis A-General, 2008)
Rare earth metal triflates, when used with ionic liquids can promote Diels-Alder reactions carried out with different dienes and dienophiles suggesting an enhancement in the catalytic power of the triflates in ionic liquids. It is possible to recover and reuse the ionic liquid phase with triflates to give comparable yields and stereoselectivities even after six cycles. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: Diels-Alder reactions; ionic liquids; rare earth metal triflates

Unusual temperature dependence of salt effects for ``on water'' wittig reaction: hydrophobicity at the interface - Tiwari, Shraeddha; Kumar, Anil (Chemical Communications, 2008)
An unusual variation with temperature of the salt effects in aqueous Wittig reaction is observed, suggesting that hydrophobic acceleration of reactions comprising ``on water'' reactants is fundamentally different from that for reactions with small non-polar solutes.

Correlations of thermodynamic properties of aqueous amino acid-electrolyte mixtures - Saritha, C.; Satpute, Dilip B.; Badarayani, Rohini; Kumar, Anil (Journal of Solution Chemistry, 2009)
Suitable equations have been proposed to correlate thermodynamic properties, like mean ion activity coefficients, volumes and compressibilities, of amino acids in electrolyte solutions. An amino acid-electrolyte-water interaction parameter is extracted from the regression of the amino acid property values in aqueous electrolyte solution that is then transferred to an expression to correlate the properties of the electrolyte in mixtures. The single interaction parameter can successfully correlate the published data on mean ion activity coefficients, apparent molar volumes and compressibilities of amino acids as well as of electrolytes in their aqueous mixtures. The equations are tested against the large number of experimental data sets available in the literature.
Keywords: Amino acids; Electrolytes; Pitzer equation; Thermodynamic properties

Dramatic change in viscosities of pure ionic liquids upon addition of molecular solvents - Khupse, Nageshwar D.; Kumar, Anil (Journal of Solution Chemistry, 2009)
Viscosities of binary mixtures of pyridinium based ionic liquids (1-butyl pyridinium tetrafluoroborate, [BP][BF(4)], 1-butyl 3-methyl pyridinium tetrafluoroborate [3-MBP][BF(4)], 1-butyl 4-methyl pyridinium tetrafluoroborate, [4-MBP][BF(4)]), and phosphonium based ionic liquids, (tetrabutyl phosphonium alaninate, [TBP][Ala]; tetrabutyl phosphonium valinate, [TBP][Val]) with the molecular solvents, water, methanol and dichloromethane, have been measured at 298.15 K. A Brookfield ultra-rheometer was employed to measure the reported viscosities. The drop in viscosity in the close vicinity of pure ionic liquid is more prominent in polar solvents like water compared to less polar solvents. The temperature dependence of this observation was also studied for binary mixtures of [4-MBP][BF(4)] with water in range of 298.15-323.15 K. The Vogel-Fulcher-Tamman (VFT) equation was employed to investigate the temperature dependence of the viscosities of pure pyridinium-based ionic liquids in the temperature range from 298.15-323.15 K.
Keywords: ionic liquids; Molecular solvents; VFT equations; viscosity

Interfacial reactivity of ``on water'' reactions in the presence of alcoholic cosolvents - Tiwari, Shraeddha; Kumar, Anil (Journal of Physical Chemistry A, 2009)
A detailed study of the variation in the interfacial reactivity and selectivity of ``on water'' reactions in the presence of increasing amounts of alcoholic cosolvents is discussed in the present work. The initial increase in the rates of ``on water'' reactions on the addition of alcoholic cosolvents is contrary to the sharp decrease in rates observed for homogeneous aqueous reactions. The existing theoretical framework is presented in terms of a typical ``on water'' process to enable a discussion of the experimental observations with reference to changing composition of the reaction medium. On the basis of the interesting observations of reactivity and selectivity variations with composition of the reaction medium, a simple ``signature'' characteristic for ``on water'' reactions is proposed.

Solubilization and conformational behavior of zein in aqueous solution of dodecyldimethylethylammonium bromide (DDAB) - Mehta, S. K.; Bhawna; Bhasin, K. K.; Kumar, Anil (Colloids and Surfaces A-Physicochemical and Engineering Aspects, 2009)
The solubilization and conformational behavior of Zein in the presence of cationic surfactant, dodecyldimethylethylammonium bromide (DDAB) have been studied. The colloidal properties of DDAB in the absence and presence of Zein have also been investigated using physico-chemical and spectroscopy methods. The surfactant appears to bind to Zein at concentrations below the critical micelle concentration (cmc) and the binding becomes weaker at concentrations above the cmc. The interaction between DDAB and Zein depends on the chemical structure and molecular parameters (conformation, molar mass, charge) of the protein. The schematic sketches of the molecular mechanisms of the complex formation between like-charged proteins and surfactants have been proposed. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Absorbance spectroscopy; Aggregation number; conductivity; DDAB; FT-IR; Surface tension; viscosity; Zein

Contrasting thermosolvatochromic trends in pyridinium-, pyrrolidinium-, and phosphonium-based ionic liquids - Khupse, Nageshwar D.; Kumar, Anil (Journal of Physical Chemistry B, 2010)
Thermosolvatochromism has been studied in three series of ionic liquids, pyridinium-based 1-butylpyridinium, 1-hexylpyridinium, and 1-octylpyridinium with bis(trifluoromethylsulfonyl)imide [NTf2] and tetrafluoroborate [BF4] anions, pyrrolidinium-based ionic liquids 1-methyl-1-butylpyrrolidium, 1-methyl-1-hexylpyrrolidium, 1-methyl-1-octylpyrrolidium with bis(trifluoromethylsulfonyl) imide anion and phosphonium-based ionic liquids tetrabutylphosphonium with alanate and valinate anions. The effect of increase in alkyl chain length and temperature on normalized polarity E-T(N), Kanilet-Taft parameters, hydrogen bond donor ability (alpha), hydrogen bond acceptor ability (beta), and polarizability (pi*) was investigated in the temperature range of 298-353 K. Interestingly, the polarity decreases with temperature in the case of pyridinium- and pyrrolidinium-based ionic liquids, and it increases with temperature in the case of phosphonium-based ionic liquids.

Ionic liquids: new materials with wide applications - Khupse, Nageshwar D.; Kumar, Anil (Indian Journal of Chemistry Section A-Inorganic Bio-Inorganic Physical Theoretical & Analytical Chemistry, 2010)
Ionic liquids have emerged as possible substitutes for volatile organic solvents and have found many applications in a variety of research areas. In this review, an effort has been made to discuss the special properties of ionic liquids that render these unique solvent media useful in chemical transformations, electrochemical applications, extractions, etc.
Keywords: Chemical processes; Electrochemical devices; ionic liquids; Physicochemical properties; Solvent properties; viscosity

Measurements and molecular interactions for N,N-dimethylformamide with ionic liquid mixed solvents - Attri, Pankaj; Reddy, P. Madhusudan; Venkatesu, P.; Kumar, Anil; Hofman, T. (Journal of Physical Chemistry B, 2010)
To understand the molecular interactions between N,N-dimethylformamide (DMF) with two families of ionic liquids (ILs), we have measured thermophysical properties such as densities (rho) and ultrasonic sound velocities (a) over the whole composition range at 25 degrees C under atmospheric pressure. The excess molar volume (V(E)) and the deviation in isentropic compressibilities (Delta K(s)) were predicted using these properties as a function of the concentration of IL. These results are fitted to the Redlich-Kister polynomials. The materials investigated in the present study included two families of ILs such as ammonium salts and imidazolium salts. Diethylammonium acetate ([Et(2)NH][CH(3)COO], DEAA), triethylammonium actetate ([Et(3)NH][CH(3)COO], TEAA), triethylammonium dihydogen phosphate ([Et(3)NH][H(2)PO(4)], TEAP), and triethylammonium sulfate ([Et(3)NH][HSO(4)], TEAS) are ammonium salts and l-benzy1-3-methylimidazolium chloride (Bmiml[Cl]) belongs to the imidazolium family. The intermolecular interactions and structural effects were analyzed on the basis of the measured and the derived properties. A qualitative analysis of the results is discussed in terms of the ion dipole, ion-pair interactions, and hydrogen bonding between ILs and DMF molecules and their structural factors.

Reversal from endothermic to exothermic behavior of imidazolium-based ionic liquids in molecular solvents - Rai, Gitanjali; Kumar, Anil (Chemical Physics Letters, 2010)
In this communication, we present an interesting reversal in the enthalpic behavior from endothermic to exothermic on increasing the carbon chain length attached to the imidazolium ring in the imidazolium-based ionic liquids. A systematic investigation is presented on the excess partial molar enthalpy, H(IL)(E) directly measured using isothermal titration calorimeter at 298.15 K for the interactions operating between cation and anion of four imidazolium ionic liquids with aqueous and various non-aqueous solvents. This reversal behavior is analyzed in terms of hydrophobic and solvation effects. (C) 2010 Published by Elsevier B.V.

Solvent-induced viscosity changes in ionic liquids - a review - Khupse, Nageshwar D.; Kumar, Anil (Proceedings of the National Academy of Sciences India Section A-Physical Sciences, 2010)
The high viscosity of several ionic liquids is an undesirable property for their applications in a variety of chemical reactions and electrochemical devices. Addition of a solvent in an ionic liquid is known to reduce its high viscosity to a great extent. In this review, an attempt has been made to examine the published data on the reduction in viscosities of many ionic liquids upon the addition of molecular solvents, including water. A tentative description has been provided for the drop in viscosities under these conditions. Analysis of the viscosity data with the help of empirical equations has been summarized. This critical review also outlines the future outlook of the required studies that might be useful to those who are interested in using ionic liquids for a variety of applications.
Keywords: ionic liquids; solvent; viscosity

Temperature dependent viscosity of mixtures of ionic liquids at different compositions - Khupse, Nageshwar D.; Kurolikar, Shabana R.; Kumar, Anil (Indian Journal of Chemistry Section A-Inorganic Bio-Inorganic Physical Theoretical & Analytical Chemistry, 2010)
This work presents experimental investigations of viscosities of the mixtures of ionic liquids, viz., [bmim][BF(4)] + [bmim][PF(6)] and [hmim][BF(4)] + [hmim][PF(6)] at different temperatures. The temperature dependence of viscosities of these mixtures has been analysed in the light of Vogel-Fulcher-Tammann (VFT) equation with excellent accuracy. The viscosities of the mixtures have been analysed using a simple mixing rule.
Keywords: ionic liquids; viscosity

Temperature effect on the molecular interactions between ammonium ionic liquids and N,N-dimethylformamide - Attri, Pankaj; Venkatesu, Pannuru; Kumar, Anil (Journal of Physical Chemistry B, 2010)
In view of the wide scope of molecular interactions between the highly polar compound of N,N-dimethylformamide (DMF) and ammonium ionic liquids (ILs), we have measured thermophysical properties such as densities (rho) and ultrasonic sound velocities (u) over the whole composition range at temperatures ranging from 25 to 50 degrees C under atmospheric pressure. To gain some insight into the several aggregations of molecular interactions present in these mixed solvents, we predicted the excess molar volume (V(E)) and the deviations in isentropic compressibilities (Delta K(s)) as a function of the concentration of IL. These results are fitted to the Redlich-Kister polynomials. The materials investigated in the present study included the hydroxide series of ammonium ILs of tetramethylammonium hydroxide [(CH(3))(4)N][OH] (TMAH), tetraethylammonium hydroxide [(C(2)H(5))(4)N][OH] (TEAH), and tetrapropylammonium hydroxide [(C(2)H(7))(4)N][OH] (TPAH). The intermolecular interactions and structural effects were analyzed on the basis of the measured and the derived properties. A qualitative analysis of the results is discussed in terms of the ion-dipole and ion-pair interactions, and hydrogen bonding between ILs and DMF molecules and their structural factors.

Activity and stability of alpha-chymotrypsin in biocompatible ionic liquids: enzyme refolding by triethyl ammonium acetate - Attri, Pankaj; Venkatesu, Pannuru; Kumar, Anil (Physical Chemistry Chemical Physics, 2011)
In view the of wide scope of structural information of biomolecules in biocompatible ionic liquids (ILs) in various applications including chemical and biochemical, it is essential to study the productive preferential interactions between biological macromolecules and biocompatible ILs. We have therefore explored the stability and activity of alpha-chymotrypsin (CT) in the presence of five ILs from different families, such as triethyl ammonium acetate (TEAA), triethyl ammonium phosphate (TEAP) from ammonium salts, 1-benzyl-3-methylimidazolium chloride ([Bzmim][Cl]), 1-benzyl-3-methylimidazolium tetrafluoroborate ([Bzmim][BF(4)]) from imidazolium salts and tetra-butyl phosphonium bromide (TBPBr) from phosphonium families. Circular dichroism (CD) and UV-vis spectrophotometer experiments were used to study CT stabilization by ILs, related to the associated structural changes and enzyme activity studies, respectively. We observed that all ILs have a dominant contribution to the stabilization of CT. The stability and activity of CT depends on the structural arrangement of the ions of ILs. Our experimental results explicitly elucidate that more hydrophobic imidazolium and phosphonium cations carrying longer alkyl chains of ILs ([Bzmim][Cl], [Bzmim][BF(4)] and TBPBr) were weak stabilizers for CT, while small alkyl chain molecules of triethyl ammonium salts (TEAA and TEAP) are strong stabilizers and therefore more biocompatible for CT stability. Our CD and NMR measurements reveal that TEAA is a refolding additive for CT from a quenched thermal unfolded enzyme structure.

Cosolvent-directed diels-alder reaction in ionic liquids - Khupse, Nageshwar D.; Kumar, Anil (Journal of Physical Chemistry A, 2011)
The rate constants of a bimolecular Diels-Alder reaction in binary mixtures of ionic liquids prepared in molecular solvents were analyzed to investigate the effect of viscosity of the medium and solvent effect. In this connection, we have carried out the Diels-Alder reaction of anthracene 9-carbinol with N-ethyl maleimide in binary mixtures of pyridinium-based ionic liquids, 1-butyl-pyridinium tetrafluoroborate, 1-buty1-3-pyridinium tetrafluoroborate, and 1-butyl-4-methyl pyridinium tetrafluoroborate in water, methanol, and chloroform at 298.15 K. The rates of reaction decreased, caused by gradually increasing the volume fraction of ionic liquids in solvents for all three ionic liquids. The kinetic results demonstrate a successful application of the pairwise interaction model built upon the concept of enforced hydrophobic hydration. A temperature-dependent study of kinetics of the Diels-Alder reaction was carried out in the binary mixtures of ionic liquids in water and was explained by the entropy-enthalpy compensation effect based upon activation parameters. Kinetics of the Diels-Alder reaction in highly aqueous medium was noted to be entropically driven.

Delineating solute-solvent interactions in binary mixtures of ionic liquids in molecular solvents and preferential solvation approach - Khupse, Nageshwar D.; Kumar, Anil (Journal of Physical Chemistry B, 2011)
The effect of solute-solvent and solvent-solvent interactions on the preferential solvation of solvatochromic indicators in binary mixtures of ionic liquids with molecular solvents has been investigated. The binary mixtures of the pyridinium-based ionic liquids 1-butylpyridinium tetrafluoroborate ([BP][BF4]), 1-butyl-3-methylpyridinium tetrafluoroborate ([3-MBP][BF4]), and 1-butyl-4-methylpyridinium tetrafluoroborate ([4-MBP][BF4]) with molecular solvents like water, methanol, and dichloromethane have been selected for this investigation. The effect of addition of ionic liquids to molecular solvents on the polarity parameters E-T(N), Kamlet-Taft parameters, hydrogen bond donor ability (HBD) (alpha), hydrogen bond acceptor ability (HBA) (beta), and polarizability (pi*) was obtained. The polarity parameters of the mixture display nonideality on addition of ionic liquids to water and dichloromethane. On the other hand, strong synergetic effects were seen in the ionic liquid-methanol binary mixtures. The preferential solvation models have been employed to analyze the collected data in order to achieve information on solute-solvent interactions in these binary mixtures.

Enthalpic approach to delineate the interactions of cations of imidazolium-based ionic liquids with molecular solvents - Rai, Gitanjali; Kumar, Anil (Physical Chemistry Chemical Physics, 2011)
We present a systematic investigation on the enthalpic assessment of the interactions operating between the cation and anion of four imidazolium ionic liquids with aqueous and various nonaqueous solvents. Accurate experimental information gathered with the help of an isothermal titration calorimeter at 298.15 K has been analyzed for excess partial molar enthalpy of the ionic liquid, H(IL)(E), in terms of hydrophobic and solvation effects. The variations in the limiting excess partial molar enthalpy of the ionic liquid, H(IL)(E infinity), have been correlated with solvent properties. We have quantified the enthalpic effects due to dissociation of ionic liquids in very dilute solutions and to clathrate formation with the increasing concentration of ionic liquid. A change in enthalpic behavior from endothermic to exothermic is observed on increasing the carbon chain length attached to the imidazolium ring. The solvent reorganization around the cationic species has been unraveled by employing the ionic liquid interaction parameters called as H(IL-IL)(E) deduced from the H(IL)(E) data. The apparent relative molar enthalpy, phi(L), derived from H(IL)(E) data has been examined in the light of the specific ion interaction theory as advanced by Pitzer with accurate results.

Eutectic mixture-directed kinetics of Diels-Alder reaction - Nagare, Amit S.; Kumar, Anil (Indian Journal of Chemistry Section A-Inorganic Bio-Inorganic Physical Theoretical & Analytical Chemistry, 2011)
In the search for environmentally benign solvent media, a new class of solvents composed of mixtures of carbohydrates with urea or methylated urea has been noted to be effective in enhancing the reaction rates of a bimolecular organic reaction like the Diels-Alder reaction of cyclopentadiene with methyl acrylate. The viscosity of these media appears to be an important parameter in controlling the second order kinetics.
Keywords: carbohydrates; Cycloaddition; Diels-Alder reaction; Dimethylurea; kinetics; Reaction rates; solvent effects; Urea; viscosity

Protic ionic liquid attenuates the deleterious actions of urea on alpha-chymotrypsin - Attri, Pankaj; Venkatesu, Pannuru; Kumar, Anil; Byrne, Nolene (Physical Chemistry Chemical Physics, 2011)
We present a biocompatible ionic liquid, triethyl ammonium acetate (TEAA), that attenuates the denaturation action of a non-ionic chaotrope, urea, on the industrially relevant proteolytic enzyme alpha-chymotrypsin.

Do anions influence the polarity of protic ionic liquids? - Shukla, Shashi Kant; Khupse, Nageshwar D.; Kumar, Anil (Physical Chemistry Chemical Physics, 2012)
Polarity studies in two classes of imidazolium-based protic ionic liquids (PILs) possessing [HSO4](-), [HCOO](-),[CH3COO](-) and [CH3CH2COO](-) anions were carried out using a solvatochromic method from 298.15 to 353.15 K. For 1-methylimidazolium class of PILs, ET(30) was found to be independent over the entire range of temperature, while ET(30) was noted to decrease with a rise in temperature in the case of 1-butylimidazolium class of PILs containing [CH3COO](-) and [CH3CH2COO](-) anions. The ET(30) value decreases in both the classes upon varying the anions ([HSO4](-), [HCOO](-), [CH3COO](-) and [CH3CH2COO](-)). The E-T(30) value is controlled by hydrogen bond acceptor basicity, b, and dipolarity/polarizability, pi*. The E-T(30) value for PILs varies inversely to the strength of the coulombic interaction between ions in PILs. Strong interactions between ions lead to lower E-T(30) values. Unlike the poor thermal effect on E-T(30), the Kamlet-Taft parameters i.e. alpha, beta and pi* have pronounced thermal effect in the imidazolium-based PILs. Variation in the Kamlet-Taft parameters is controlled by the stabilization of ions and the degree of proton transfer from Bronsted acid to Bronsted base.

High viscosity of ionic liquids causes rate retardation of Diels-Alder reactions - Kumar, Anil; Pawar, Sanjay S. (Science China-Chemistry, 2012)
Second order rate constants, k (2) have been determined for three bi-molecular Diels-Alder reactions to demonstrate that the high viscosity of ionic liquids can be a detrimental property in carrying out Diels-Alder reactions, if ionic liquids are employed as solvent media. It is possible to enhance the reaction rates of the reaction if a co-solvent is mixed in pure ionic liquid used as a solvent.
Keywords: Diels-Alder reactions; ionic liquids; kinetics; viscosity

Probing the mechanism of baylis-hillman reaction in ionic liquids - Singh, Anshu; Kumar, Anil (Journal of Organic Chemistry, 2012)
The kinetic data for a Baylis-Hillman reaction in certain ionic liquids possessing ethylsulfate anion [EtSO4](-) demonstrate that the rate determining step (RIDS) is second order in aldehyde, but first order in acrylate and DABCO. This observation is similar to the one made by McQuade et al., who carried out this reaction in an aprotic polar solvent like DMSO. However, this is in contrast to the general observation that ADS is first order in aldehyde, acrylate, and DABCO in organic solvents.

Probing thermal interactions of ionic liquids with dimethyl sulfoxide - Rai, Gitanjali; Kumar, Anil (Chemphyschem, 2012)
Interactions between ionic liquids and dimethyl sulfoxide (DMSO) are probed by isothermal titration calorimetry. The excess partial molar enthalpies of ionic liquids H-IL(E) in DMSO are discussed in terms of solutesolvent interactions. The specific interaction theory originally developed by Pitzer is used to analyze the apparent molar enthalpy phi(L) of ionic liquids in DMSO with the help of ion-interaction parameters. Furthermore, quantitative information on solvent reorganization and clathrate formation is obtained and interpreted.
Keywords: calorimetry; dimethyl sulfoxide; ionic liquids; solvent effects; thermochemistry

Viscosity dependence of intra- and intermolecular diels-alder reactions - Tiwari, Shraeddha; Kumar, Anil (Journal of Physical Chemistry A, 2012)
The kinetics of the bimolecular Die Is Alder reaction between anthracene-9-carbinol and N-ethyl maleimide have been studied in a series of pyridinium-based ionic liquids with the tetrafluoroborate ([BF4](-)) and the bis(trifluorosulfonimide) ([NTf2](-)) anions and the viscosity dependence of the rate constants have been compared with the results for the intramolecular Diels Alder reaction of (E)-1-phenyl-4-[2-(3-methyl-2-butenyloxy)benzylidene]-5-pyrazolone. The comparison leads to the surprising observation that the intermolecular reaction is less susceptible to viscosity variations of the ionic liquids as compared to the intramolecular reaction. The observed similarities and differences emphasize the complicated nature of solvent friction on the kinetics of cycloaddition reactions. The results are explained by considering the bimolecular and intramolecular processes as cases of translational and rotational diffusion, respectively. Plausible indicators of microviscosity consistent with the kinetic data for the Diels-Alder reactions are briefly discussed along with the constraints involved in designing a general microviscosity scale.

Water and a protic ionic liquid acted as refolding additives for chemically denatured enzymes - Attri, Pankaj; Venkatesu, P.; Kumar, Anil (Organic & Biomolecular Chemistry, 2012)
In this communication, we present the ability of water and a protic ionic liquid, triethyl ammonium phosphate (TEAP) to act as refolding additives for the urea-induced chemical denaturated state of the two enzymes, alpha-chymotrypsin and succinylated Con A. We show that the enzymatic activity is regained and in certain circumstances enhanced.

Do protic ionic liquids and water display analogous behavior in terms of hammett acidity function? - Shukla, Shashi Kant; Kumar, Anil (Chemical Physics Letters, 2013)
We address an issue whether the strength of carboxylic acids in water is linear with respect to that in ionic liquids. Strength of carboxylic acids in water and different PILs using Hammett function (Ho) has revealed interesting linear correlation between the Ho function for all acids in PILs and PIL-water in spite of large structural and electronic differences. These observations suggest that different structural and electronic features of PILs and water behave analogously towards Ho. This linearity in Ho functions between PILs and PIL-water systems can be used to develop predictive method to calculate Ho values. (c) 2013 Elsevier B.V. All rights reserved.

Hydrophobic and hydrophilic balance and its effect on mesophase behaviour in hydroxyalkyl ethers of methyl glucopyranoside - Singh, Madan K.; Xu, Rui; Moebs, Sylvie; Kumar, Anil; Queneau, Yves; Cowling, Stephen J.; Goodby, John W. (Chemistry-A European Journal, 2013)
Four series of monosubstituted methyl -D-glucopyranoside hydroxyalkyl ethers were prepared and their thermotropic and lyotropic self-organising properties were investigated in terms of the hydrophobichydrophilic balance with respect to their molecular structures. The results obtained lead us to a new understanding of the forces that drive the formation of condensed soft-matter phases.
Keywords: carbohydrates; liquid crystals; mesophases; Self-assembly; soft matter

Interesting thermal variations owing to cationic ring structural features in protic ionic liquids - Rai, Gitanjali; Kumar, Anil (Physical Chemistry Chemical Physics, 2013)
The present communication divulges interesting thermal behavior of different protic ionic liquids arising due to the hydrophobicity modifications in their parent cationic ring structures. This work assists us in differentiating between protic ionic liquids, their aprotic counterparts and common electrolytes in water. The thermal signatures produced by protic ionic liquids, aprotic ionic liquids and electrolytes emerge as individual fingerprints for them.

Probing the acidity of carboxylic acids in protic ionic liquids, water, and their binary mixtures: activation energy of proton transfer - Shukla, Shashi Kant; Kumar, Anil (Journal of Physical Chemistry B, 2013)
Acidity functions were used to express the ability of a solvent/solution to donate/accept a proton to a solute. The present work accounts for the acidity determination of HCOOH, CH3COOH, and CH3CH2COOH in the alkylimidazolium-based protic ionic liquids (PILs), incorporated with carboxylate anion, water, and in a binary mixture of PIL and water using the Hammett acidity function, H-0. A reversal in the acidity trend was observed, when organic acids were transferred from water to PIL. It was emphasized that an increased stabilization offered by PIL cation toward the more basic conjugate anion of organic acid was responsible for this anomalous change in acidity order in PILs, which was absent in water. The greater stabilization of a basic organic anion by PIL cation is discussed in terms of the stable hard-soft acid base (HSAB) pairing. A change in the H-0 values of these acids was observed with a change in temperature, and a linear correlation between the ln H-0 and 1/T was noted. This relationship points toward the activation energy of proton transfer (E-a,E-H+), a barrier provided by the medium during the proton transfer from Bronsted acid to indicator. The H-0 function in binary mixtures points to the involvement of pseudosolvent, the behavior of which changes with the nature and concentration of acid. The presence of the maxima/minima in the H-0 function is discussed in terms of the synergetic behavior of the pseudosolvent composed of the mixtures of aqueous PILs.

Unusual salting effects in ionic liquid solutions - Nanda, Raju; Kumar, Anil (Indian Journal of Chemistry Section A-Inorganic Bio-Inorganic Physical Theoretical & Analytical Chemistry, 2013)
Unusual salting effects of salting-out agents like LiCl and NaCl and salting-in agents like LiClO4 and NaClO4 in ionic liquid solutions are reported. It is observed that the salting behavior in water can be altered in the presence of ionic liquids. It is demonstrated that the salting-in agents in the presence of the ionic liquids with higher alkyl chain can display unusual fall and rise in the viscosity of the systems. On the other hand, no change in the behavior of the salting-out agents is noted in these ionic liquids. A tentative explanation is proposed for the observed viscosity data in these systems.
Keywords: Cationic ring; ionic liquids; Salting effects; viscosity

Why does water accelerate organic reactions under heterogeneous condition? - Manna, Arpan; Kumar, Anil (Journal of Physical Chemistry A, 2013)
An exhaustive kinetic analysis has been carried out to offer the convincing evidence of the involvement of the oil water interface in guiding ``on water organic reaction'' mechanism. We have tuned the interface to prove its indispensable efficacy to make on water reaction a unique type among water mediated organic reactions. Sensitive techniques have established the preferential salvation of polarizable ions at the water surface. The experimental methods have been developed to control the molecular structure of oil water interface in situ. Temperature-dependent analyses have also been presented to understand the enthalpic and entropic modifications of the interfacial water molecules during a heterogeneous reaction. Both of our kinetic and thermodynamic outcomes have univocally established that the hydrogen-bonding ability of the surface water molecules plays a critical role in deciding the on water organic reaction mechanism. The results have important implications on understanding the role of small water molecules adjacent to the reactants during the reactions discussed in this investigation.

Atypical energetic and kinetic course of excited-state intramolecular proton transfer (ESIPT) in room-temperature protic ionic liquids - Manna, Arpan; Sayed, Mhejabeen; Kumar, Anil; Pal, Haridas (Journal of Physical Chemistry B, 2014)
The excited-state intramolecular proton-transfer (ESIPT) process in 1,8-dihydroxyanthraquinone (18DHAQ) dye has been investigated in protic ionic liquid (PIL) solvents using photochemical measurements. The results demonstrate noteworthy modulations in both steady-state and time-resolved emission characteristics of excited normal (N*) and tautomeric (T*) forms of the dye. That the emission of T* increases unexpectedly upon increasing solvent viscosity indicates that subsequent to the initial forward ESIPT, there is also a relatively slower back ESIPT process involved for the excited dye. It is inferred that the propensity of this back ESIPT process is determined by the dynamics of the diffusive solvent relaxation, a process that is known to be strongly viscosity-dependent in ionic liquids. Evidence of both forward and back ESIPT for the dye has been obtained from femtosecond fluorescence up-conversion measurements. While an unusually fast forward ESIPT is clearly observed in all of the PILs studied, the uncommon back ESIPT process is distinctly indicated in PIL solvents having lower viscosities, certainly due to reasonably fast diffusive solvent relaxation in these solvents that causes a temporal modulation in the energies of the normal and tautomeric forms within a reasonably short time and thereby brings down the energy of N* compared to that of T*, triggering the back ESIPT process. Observation of solvent-viscosity-dependent back ESIPT is an intriguing finding for the present study as to the best of our knowledge, such a behavior has so far not been reported in the literature for the ESIPT reaction.

Calorimetric elucidation of ionic interactions in room temperature ionic liquid solutions - Rai, Gitanjali; Kumar, Anil (Clean Technologies and Environmental Policy, 2014)
Knowledge of thermal properties of room temperature ionic liquid (RTIL) solutions is essential in chemical process designing in addition to their application in understanding ionic interactions at molecular level. RTILs are considered to be substitutes for volatile organic compounds. While some experimental thermal data on these systems are available in a random manner, the modeling efforts to correlate enthalpy-concentration profiles of RTIL solutions are very scanty. In this review, an effort has been made to compare and discuss the experimental data of these RTIL solutions available in the literature. The readers are also made aware of the disappointing situation regarding the availability of any type of correlative models for the enthalpy-concentration data of the RTIL systems. An accurate knowledge of activity coefficients at infinite dilutions, Iyen (i) (a) acquired from thermal data will serve as inputs for the newer less polluting process designing and thus open opportunity for a cleaner environment.
Keywords: Calorimeters; Correlative models; Excess partial molar enthalpy; Room temperature ionic liquids

Elucidation of ionic interactions in the protic ionic liquid solutions by isothermal titration calorimetry - Rai, Gitanjali; Kumar, Anil (Journal of Physical Chemistry B, 2014)
The strong hydrogen-bonded network noted in protic ionic liquids (PILs) may lead to stronger interactions of the ionic entities of PILs with solvents (water, methanol, ethylene glycol, climethylsulfoxide (DMSO), N,N'-dimethylformamide (DMF)) as compared with those of aprotic ionic liquids (APILs). The PILs used in this work are 1-methylimidazolium tetrafluoroborate, 2-methylpyridinium tetrafluoroborate, and N-methylpyrrolodinium tetrafluoroborate in comparison to 1-butyl-3-methylimidazolium tetrafluoroborate, which is classified as an APIL. In this work, the excess partial molar enthalpy, H-IL(E) obtained from isothermal calorimetric titrations at 298.15 K is used to probe the nature of interactions of the PIL cations with solvent molecules against those present in APIL solvent systems. This work also reports interesting flip-flopping in the thermal behavior of these PIL-solvent systems depending upon the structure of the cationic ring of a PIL. In some cases, these flip-flops are the specific fingerprints for specific PILs in a common solvent environment. The excess partial molar enthalpy at infinite dilution, H-IL(E,infinity), of these PILs bears a critical dependence on the solvent properties. An analysis of relative apparent molar enthalpies, phi(L), of the PIL solutions by the ion interaction model of Pitzer yields important information on ionic interactions of these systems.

Invoking pairwise interactions in water-promoted diels-alder reactions by using ionic liquids as cosolvents - Manna, Arpan; Kumar, Anil (Chemphyschem, 2014)
Rate constants and derived activation parameters of organic reactions in aqueous media, in particular Diels-Alder reactions, are sensitive to the presence of cosolvents in water. To enhance the solubility window of water, we introduced ionic liquids as cosolvents in the aqueous Diels-Alder reaction between anthracene-9-carbinol and N-ethylmaleimide. The reactive potentials of the organic compounds are parameterized by using semi-empirical quantum chemical methods. The principle of Savage-Wood additivity of group interactions is used to quantify the pairwise group interactions among chemically inert ionic liquids and organic reactants, both at initial and transition states of the reaction. The present approach shows promise, as the use of simple calculations from easily available kinetic data can help researchers to understand the versatility of green ionic-liquid alternatives to volatile organic solvents.

Observation of the marcus inverted region for bimolecular photoinduced electron-transfer reactions in viscous media - Kumbhakar, Manoj; Manna, Arpan; Sayed, Mhejabeen; Kumar, Anil; Pal, Haridas (Journal of Physical Chemistry B, 2014)
The general observation of Marcus inverted region (MIR) for bimolecular electron-transfer (ET) reactions in different viscous media, e.g., micelles, reverse micelles, vesicles, ionic liquids, DNA scaffold, etc. has been doubted in some recent publications arguing limitations in SternVolmer (SV) analysis to account for the static and transient stages of quenching in these slow diffusing media. Thus, following a theoretical treatment based on a spherically symmetric diffusion equation coupled with conventional Marcus ET description, it has been suggested that the MIR observed in viscous media arises due to the inadequate consideration of different quenching regimes and also due to the differential excited-state lifetimes of the fluorophores used than a genuine one (J. Am. Chem. Soc. 2012, 134, 11396). However, the overall treatment in this study is severely compromised by setting the minimum solvent reorganization energy (?s) to (lambda) to similar to 0.96 eV while fitting the experimental data, which unambiguously suggests that the inversion in ET rate will never appear in the exergonicity (-Delta G(0)) range of 0.16 to 0.71 eV, as is the case for the studied ET systems. Besides, the applicability of the conventional Marcus ET model (instead of Sumi-Marcus two-dimensional ET model) in such extremely viscous media with exceptionally slow solvent response is highly debatable and perhaps is the main cause of the failure in fitting the experimental data quite satisfactorily. In the present study involving ultrafast ET quenching for coumarin derivatives by dimethylaniline donor in viscous ionic liquid media, we demonstrate clear MIR for the intrinsic ET rates, directly obtained from the ultrafast decay components of 110 ps, a time scale in which diffusion of reactants is negligible and the ET rates are either faster than or, at the most, competitive with the solvent reorganization. The appearance of MIR at ?Delta G(0) similar to-0.5 eV, significantly lower than expected from the lambda(s) value, further substantiate the nonapplicability of conventional ET description but certainly advocate for the applicability of the SumiMarcus two-dimensional ET model in such media. Moreover, no obvious correlation has experimentally been observed between the excited-state lifetimes of the coumarin derivatives and the ET rates for a large number of dyes used in the present study. On the basis of the present results and drawing inferences from reported literatures in viscous media, we conclude that not only is the appearance of MIR very genuine but also the mechanistic model necessary to account the observed facts for the bimolecular ET reactions in a viscous medium is the two-dimensional ET description, which deals with an extremely slow relaxing solvent coordinate and a fast relaxing intramolecular coordinate to describe the ET reactions.

Quantitative evaluation of the ability of ionic liquids to offset the cold-induced unfolding of proteins - Kumar, Awanish; Rani, Anjeeta; Venkatesu, Pannuru; Kumar, Anil (Physical Chemistry Chemical Physics, 2014)
Significant non-reversible two-state denaturation was observed for proteins such as myoglobin (Mb) and alpha-chymotrypsin (CT) with decreasing temperature in the presence of 1-butyl-3-methylimidazolium-based ([C(4)mim]X-+(-)) ionic liquids (ILs) with various anions (X-). Interestingly, for the first time, ILs having acetate and bromide anions were proven to counteract the cold-induced unfolding of proteins.

Deviation of polarity from linearity in liquid mixtures containing an ionic liquid - Beniwal, Vijay; Shukla, Shashi K.; Kumar, Anil (Physical Chemistry Chemical Physics, 2015)
The physico-chemical properties of liquid mixtures, in general, exhibit deviations from linear behaviour with respect to their composition, arising out of different types of cross-intermolecular interactions (both specific and non-specific). These specific and non-specific interactions can however be monitored to obtain the linear mixing in liquid mixtures using the pseudo-solvent methodology in such a manner that the interactions causing deviations from linearity are cancelled out and mixtures display linear behaviour.

Dissociation of equimolar mixtures of aqueous carboxylic acids in ionic liquids: role of specific interactions - Shukla, Shashi Kant; Kumar, Anil (Journal of Physical Chemistry B, 2015)
Hammett acidity function observes the effect of protonation/deprotonation on the optical density/absorbance of spectrophotometric indicator. In this work, the Hammett acidity, H-0, of equirriolar mixtures of aqueous HCOQH, CH3COOH, and CH3CH2COOH was measured in 1-methylimidazolium-, 1-methylpyrrolidinium-, and 1-methylpiperidinium-based protic ionic liquids (PILs) and 1-buty1-3-methylimidazolium-based aprotic ionic liquid (AIL), with formate (HCOO-) anion. Higher H-0 values were observed for the equimolar mixtures of aqueous carboxylic acids in protic ionic liquids compared with those of the aprotic ionic liquid because of the involvement of the stronger specific interactions between the conjugate acid of ionic liquid and conjugate base of carboxylic acids as suggested by the hard soft acid base (HSAB) theory. The different Ho values for the equimolar mixtures of aqueous carboxylic acids in protic and aprotic ionic liquids were noted to depend on the activation energy of proton transfer (E-a,H(+)). The higher activation energy of proton transfer was obtained in AIL indicating lower ability to form specific interactions with solute than that of PILs. Thermodynamic parameters determined by the ``indicator overlapping method'' further confirmed the involvement of the secondary interactions in the dissociation of carboxylic acids. On the basis of the thermodynamic parameter values, the potential of different ionic liquids in the dissociation of carboxylic acids was observed to depend on the hydrogen bond donor acidity (alpha) and hydrogen bond acceptor basicity (beta), characteristics of specific interactions.

Experimental signature of microheterogeneity in ionic liquid-H2O systems and their perturbation by adding Li+ salts: a pulsed gradient spin-echo NMR approach - Nanda, Raju; Rajamohanan, P. R.; Kumar, Anil (Chemphyschem, 2015)
Distinct microheterogeneity has been observed in the [OMIM]Br-H2O system, which is interestingly perturbed by the addition of Li+ salts, indicating unusual diffusivity of [OMIM]Br and H2O molecules. However, the diffusional dynamics of water clusters show contrasting salting behavior at higher concentrations of Li+ salts, following the classical salting phenomenon in lower amounts. In contrast, the existing microheterogeneity in the [BMIM]Br-H2O system is weak enough to show any perturbation caused by the Li+ salts on the NMR time scale.
Keywords: ionic liquids; lithium; microheterogeneity; salt effect; viscosity

Interesting viscosity changes in the aqueous urea-ionic liquid system: effect of alkyl chain length attached to the cationic ring of an ionic liquid - Nanda, Raju; Rai, Gitanjali; Kumar, Anil (Journal of Solution Chemistry, 2015)
In the present article, we demonstrate the effect of urea on the structure of the ionic liquids in their aqueous solutions through viscometric methods. We unravel the structure altering effect of urea in its aqueous solutions of ionic liquids possessing higher alkyl chains. The finding is an attempt to discern the anomalous behavior of urea as shown in the past with the help of many techniques. Interestingly, in the aqueous solutions of the imidazolium based ionic liquids having substitution of -C4H9 and -C6H13 groups on the imidazolium ring, urea exhibits kosmotropic behavior. Further increase in the substituted alkyl group such as -C8H17 alters the urea behavior to be chaotropic.
Keywords: Alkyl chain length; ionic liquids; Structure-breaker; Structure-maker; Urea; viscosity

Kinetic and mechanistic investigations of the Baylis-Hillman reaction in ionic liquids - Singh, Anshu; Kumar, Anil (RSC Advances, 2015)
We report here a quantitative study of the kinetics and mechanism of the Baylis-Hillman reaction in the presence of ionic liquids as solvent media. Apparently, a simple Baylis-Hillman reaction can occur by two different exclusive mechanisms in ionic liquids. The delicate balance of these mechanisms is maintained by the ionic environment employed. The main features of the possible mechanism have been described here along with interesting kinetic consequences. The measurement of rate constants and activation energy parameters demonstrate that as the medium becomes basic, the order of the reaction changes from 1 to 2. An unexpected change in the mechanism of the reaction is observed with a change in the nature of the ionic liquid. The Linear Solvation Energy Relationship has also been used as an investigating tool to delineate the respective contributions of the cation and anion of the ionic liquid. The observation strongly dictates the dependency of the mechanism of the Baylis-Hillman reaction on the nature of the anion of the ionic liquids undertaken for this study.

Phase behavior, diffusion, structural characteristics, and pH of aqueous hydrophobic ionic liquid confined media: insights into microviscosity and microporsity in the [C(4)C(4)im][NTf2] + water system - Nanda, Raju; Kumar, Anil (Journal of Physical Chemistry B, 2015)
We present our studies on the physicochemical properties of water confined in Dibutylimidazolium bis(trifluoromethanesulfonylimide) ([C(4)C(4)im][NTf2]) reverse micelles through the NMR relaxation measurements that provide us an understanding of microviscosity and pH in the confined condition. We present experimental results on phase behavior, diffusion, structural characteristics and pH in aqueous ionic liquid-confined media. The ternary phase diagram was constructed by the cloud point measurements and the microheterogeneous regions were detected by the measurement of bulk viscosity and diffusion coefficients of K-4[Fe(CN)(6)] inside the homogeneous microemulsion systems through the cyclic voltammetric (CV) measurements. The size of the microemulsion systems was characterized by the dynamic light scattering (DLS) method. The H-1 NMR spectra of homogeneous microemulsion systems were taken which indicates the presence of bound and free water molecules inside the microemulsion system. The NMR spinlattice relaxation time (T-1) of water molecules in its homogeneous microemulsion systems were measured and the reorientational correlation time (t(c)) of water molecules obtained from it indicates that the fluidity of homogeneous confined media decreases with the decrease in the composition of water. Microviscosity of the aqueous confined media was calculated from the measured T-1 relaxation time values by applying the DebyeStokes equation and correlated with the bulk viscosity of the samples. It was observed that both the microviscosity and bulk viscosity show inverse relationship. The fraction of bound and free water molecules were calculated from the measured T-1 values. NMR spinspin relaxation time (T-2) of water molecules in its homogeneous microemulsion systems were measured with the varying pH of the aqueous core. A change in the T-2 relaxation time of the water proton was observed proposing an exchange of proton between the H2O and -OH group of the TX-100 molecules. Finally, methyl orange (MO) was used as a UVvis spectrophotometric molecular probe and the measured lambda(max) values of the probe were used for the detection of micropolarity of the homogeneous aqueous confined media and was found to be increase with the increase in the size of the confined media.

Polarity issues in room temperature ionic liquids - Shukla, Shashi Kant; Kumar, Anil (Clean Technologies and Environmental Policy, 2015)
The study on ionic liquids has occupied an important place in chemical processes because of several beneficial properties. In order to use these ionic liquids as solvent media in chemical processes, it is essential to know their solvent properties. In this review, an attempt has been made to critically evaluate and discuss the polarity parameters of ionic liquids. The experimental polarity data on ionic liquids are not yet available for numerous ionic liquids. This review will serve as a guideline to investigate polarity issues of these materials and emerge with a simple, but still sound theoretical or semi-empirical models to account for the variation in polarity in the ionic liquid solutions.

Solvent-mediated molar conductivity of protic ionic liquids - Thawarkar, Sachin; Khupse, Nageshwar D.; Kumar, Anil (Physical Chemistry Chemical Physics, 2015)
The molar conductivity, A(m), of protic ionic liquids (PILs) in molecular solvents is measured at 298.15 K. The decrease in the A(m) values of PILs is observed with an increase in the concentration of PILs. The limiting molar conductivities, A(m)(0), were obtained for each PIL in different molecular solvents using a least squares method. The A(m)(0) data for PILs were correlated with the structural aspects of PILs and solvent properties. The polar protic solvents show poor ionic association as compared to the polar aprotic solvents, which is discussed on the basis of the hydrogen bond donating (HBD) ability of solvents and PILs. The alkyl chain substitution of anions plays a significant role in the ionic association of the PILs. The diffusion coefficient D-0 and the transport number t were determined, which were consistent with the A(m)(0) values of PILs in water. The A(m)(0) and D-0 values are dependent on the hydrodynamic radius of anions of these ionic liquids. The extent of ionic association for each PIL was discussed using temperature dependent A(m) data for aqueous PIL systems in terms of the Walden plot.

Synergistic effects and correlating polarity parameters in binary mixtures of ionic liquids - Beniwal, Vijay; Kumar, Anil (Chemphyschem, 2015)
Understanding how a chemical reaction proceeds in solution requires precise knowledge of solute-solvent interactions. Certain issues involved in ionic liquid binary mixtures are still not clearly understood, including: 1) the effects of hydrogen-bond-acceptor basicity () of solvents on the synergistic effects found in ionic liquid-alcohol mixtures, 2) the interrelation between the polarity parameters in binary mixtures, and 3) the application of a model for the description of normalised electronic transition energy for all the binary mixtures. Here, a detailed analysis of polarity parameters in both hydrophilic and hydrophobic ionic liquids has been carried out. A three-parameter model developed by Roses et al. [J. Chem. Soc. Perkin Trans. 2 1997, 13411348] was found to be applicable to all the binary mixtures, and synergistic effects are generated as a result of high values of alcohols compared with those of the ionic liquids. A strong correlation was observed in the values and hydrophobicities of pure ionic liquids, suggesting that values can play a role in describing synergism.
Keywords: green chemistry; ionic liquids; liquids; noncovalent interactions; solvent effects

Water-promoted diels-alder reaction in quaternary ammonium salts - Nagare, Amit S.; Manna, Arpan; Sonawane, Pramod D.; Kumar, Anil (Journal of Physical Organic Chemistry, 2015)
{Prevailing classification of salts based on their effect in solubility and stability of proteins in aqueous solution predicts that tetraalkylammonium salts, guanidinium chloride (GnCl), LiClO4 act as salting-in (S/I) and LiCl, NaCl act as salting-out (S/O) in aqueous conditions. In the same context the behaviour of GnCl, LiClO4 and LiCl are contradictory in polar solvents like ethylene glycol and formamide. In these solvents, expected salt effect shows just opposite nature from their usual expectation. However, in the aqueous solution salts like tetraalkylammonium halide (R4NX
Keywords: Delta G(solvation); Diels-Alder reaction; k(s); kinetic study; solubility; tetraalkylammonium salts; viscosity

Can a diels-alder reaction accelerate in a supersaturated solvent at room temperature? - Nagare, Amit S.; Manna, Arpan; Kumar, Anil (New Journal of Chemistry, 2016)
A new supersaturated solvent is proposed to accelerate the Diels–Alder reaction between cyclopentadiene and methyl acrylate by several times. The proposed supersaturated solvent consists of various carbohydrates, organic acid and organic ketone in water, beyond their solubility limits in water, at room temperature. The results demonstrate that the presence of excess –OH groups from the carbohydrates plays a pivotal role leading to the increased reactivity and selectivity of the Diels–Alder reaction. The role of hydrogen bond accelerators and polarity of the solvent have been analyzed through a comparative study of the same reaction in similar green solvents. Collision-controlled reaction theory has been invoked to understand the role of encounter complexes to accelerate such a reaction at the molecular level in such highly viscous supersaturated solvent. No detrimental effects from the high viscosity of the new solvent medium on the reaction kinetics was been noted.

Comparative investigation of the ionicity of aprotic and protic ionic liquids in molecular solvents by using conductometry and NMR spectroscopy - Thawarkar, Sachin; Khupse, Nageshwar D.; Kumar, Anil (Chemphyschem, 2016)
Electrical conductivity (sigma), viscosity (), and self-diffusion coefficient (D) measurements of binary mixtures of aprotic and protic imidazolium-based ionic liquids with water, dimethyl sulfoxide, and ethylene glycol were measured from 293.15 to 323.15K. The temperature dependence study reveals typical Arrhenius behavior. The ionicities of aprotic ionic liquids were observed to be higher than those of protic ionic liquids in these solvents. The aprotic ionic liquid, 1-butyl-3-methylimidazolium tetrafluoroborate, [bmIm][BF4], displays 100% ionicity in both water and ethylene glycol. The protic ionic liquids in both water and ethylene glycol are classed as good ionic candidates, whereas in DMSO they are classed as having a poor ionic nature. The solvation dynamics of the ionic species of the ionic liquids are illustrated on the basis of the (HNMR)-H-1 chemical shifts of the ionic liquids. The self-diffusion coefficients D of the cation and anion of [HmIm][CH3COO] in D2O and in [D-6]DMSO are determined by using H-1 nuclei with pulsed field gradient spin-echo NMR spectroscopy.
Keywords: conducting materials; Electrochemistry; electrostatic interactions; Ion pairs; ionic liquids

Concentration-dependent apparent partition coefficients of ionic liquids possessing ethyl-and bi-sulphate anions - Jain, Preeti; Kumar, Anil (Physical Chemistry Chemical Physics, 2016)
This study deals with the concentration dependent apparent partition coefficients log P of the ethyl and bisulfate-based ionic liquids. It is observed that the bisulfate-based ionic liquids show different behaviour with respect to concentration as compared to ethyl sulphate-based ionic liquids. It is significant and useful analysis for the further implementation of alkyl sulfate based ionic liquids as solvents in extraction processes. The log P values of the ethyl sulphate-based ionic liquids were noted to vary linearly with the concentration of the ionic liquid, whereas a flip-flop trend with the concentration for the log P values of the bisulphate-based ionic liquids was observed due to the difference in hydrogen bond accepting basicity and possibility of aggregate formation of these anions. The pi-pi interactions between the imidazolium and pyridinium rings were seen to affect the log P values. The alkyl chain length of anions was also observed to influence the log P values. The hydrophobicity of ionic liquid changes with the alkyl chain in the anion in the order; [HSO4](-) < [EtSO4](-) < [BuSO4](-).

Isothermal titration calorimetric study of the ionic liquid solutions in alcohols in extreme dilutions: an investigation of ion-solvent interactions - Rai, Gitanjali; Jain, Preeti; Kumar, Anil (Journal of Solution Chemistry, 2016)
In this work an effort has been made to show the effect of an alcohol-rich environment on imidazolium-based ionic liquids at 298.15 K using an isothermal titration calorimeter. It is divulged from this study that the thermal behavior expressed in terms of excess partial molar enthalpy, \( H_{\text{IL}}^{\text{E}} \), of ionic liquids in various linear alcohols is governed by the increasing hydrophobicity of the residual alkyl group attached to the cation of an ionic liquid and to the alcohol molecules. An interesting observation about the systems consisting of ethylated residuals on both the cations of the ionic liquid and the alcohol molecules is that these systems do not follow the trend exhibited by other ionic liquid–alcohol systems. Interesting information on ionic interactions is obtained by using a simple methodology that gives the enthalpic interaction parameter \( H_{{I{\text{L - IL}}}}^{\text{E}} \).
Keywords: Ionic liquidsAlcoholsExcess enthalpyIsothermal titration calorimeter

Spectacular rate enhancement of the diels-alder reaction at the ionic liquid/n-hexane interface - Beniwal, Vijay; Manna, Arpan; Kumar, Anil (Chemphyschem, 2016)
The use of the ionic liquid/n-hexane interface as a new class of reaction medium for the Diels-Alder reaction gives large rate enhancements of the order of 10(6) to 10(8) times and high stereoselectivity, as compared to homogeneous media. The rate enhancement is attributed to the H-bonding abilities and polarities of the ionic liquids, whereas the hydrophobicity of ionic liquids was considered to be the factor in controlling stereoselectivity.
Keywords: Diels-Alder reaction; Interfaces; ionic liquids; kinetics; stereoselectivity

Understanding positive and negative deviations in polarity of ionic liquid mixtures by pseudo-solvent approach - Beniwal, Vijay; Kumar, Anil (Physical Chemistry Chemical Physics, 2016)
Physico-chemical properties of liquid mixtures in general display large deviations from linear behaviour, arising out of complex specific and non-specific intermolecular interactions. The polarity of liquid mixtures displaying large positive and negative deviations can be minimized and linear mixing can be achieved in liquids using a pseudo-solvent methodology. The work described herein is designed to investigate the influence of different physical parameters on the linear pseudo-solvent composition in ionic liquid mixtures. For this purpose, we have determined the deviations from linearity, Delta E-T(N) values (defined as Delta E-T(N) = E-Texp.(N) - E-Tlin mix.(N) with E-Tlin mix.(N) given by Sigma(n)(i=0) E-Ti(N0) x(i)) for binary mixtures of a variety of ionic liquids, including two molecular solvents, DMSO and formamide. Firstly, the investigations were carried out in three 1-butyl-3-methylimidazolium cation based aprotic ionic liquids and the roles of anionic structure and hydrogen bond acceptor basicities (beta values) of the ionic liquids were determined. The influence of the cationic structure, i.e., the hydrogen bond donor acidity (alpha values) and non-associative nature of the ionic liquids, was determined using C2-methylated analogs, 1-butyl-2,3-dimethylimidazolium cation based ionic liquids. The role of the protic nature of ionic liquids was studied in two protic ionic liquids, viz., 1-methylimidazolium formate and 1-methylimidazolium acetate. The effects of the temperature, pseudo-solvent structure and solvatochromic probe structure on the Delta E-T(N) values were also explored.

Comparable ionicity of the solutions of aprotic and protic ionic liquids by anion substitution - Jain, Preeti; Kumar, Anil (Journal of Solution Chemistry, 2017)
Temperature dependent molar conductances and fluidities of bisulfate and ethyl sulfate anion-based ionic liquids were measured. The extent of dissociation of the ionic liquids was estimated from the Walden plot in term of ionicity. The ionicity mainly depends on the magnitude of Coulombic forces, altered by the anion’s Lewis basicity. Aqueous solutions of aprotic ionic liquids, in general, possesses ionicity in the range of ≈70–99%. This article reveals that the substitution of the anion by bisulfate and ethylsulfate reduces the ionicity of aqueous solution of these ionic liquids to the range of 10–37%. This is very close to that exhibited by some of the protic ionic liquids and phosphonium based ionic liquids with sweetner anions. The concentration dependent molar conductance of these ionic liquids has been fitted to Mahiuddin and Ismail’s equation. To our surprise, the molar conductances of bisulfate-based aprotic ionic liquids are remarkably high, even though these ionic liquids possess lower ionicity.

Introducing the bipolar solvent media using the aqueous mixtures of amino acid anion-based ionic liquids - Beniwal, Vijay; Kumar, Anil (Journal of Physical Chemistry B, 2017)
To carry out a chemical reaction between the reactants with largely different polarities, it becomes important to have a reaction medium that possesses both the polar and nonpolar solvation environments. In an attempt to explore the reaction media with such unique polarity properties, the present study provides a thorough understanding of the bipolar solvent media using the aqueous mixtures of amino acid anion-based ionic liquids. The highly polar behavior of the binary mixtures used in the study has been ascribed to the pure ionic liquid state. However, the less polar solvation shells have been attributed to the presence of a neutral form of the anions. Addition of water in the amino acid anion-based ionic liquids causes the protonation of a certain fraction of the anions of the ionic liquids, resulting into the formation of a less polar nonionic protonated form along with the highly polar natural anionic form. This results into the formation of two solvation spheres with different polarities, which can be seen very clearly from the presence of two absorption bands (lower wavelength absorption band and higher wavelength absorption band) in the UV-vis absorption spectrum of Reichardt's E-T(30) dye and two emission bands (lower wavelength emission band and higher wavelength emission band) in the fluorescence emission spectrum of C481 dye. The values of the E-T(N) polarity parameter corresponding to the two solvation shells having different polarities have been calculated from the deconvoluted absorption spectra of the Reichardt's E-T(30) and were analyzed in three amino acid anion-based ionic liquids. Generation of the neutral form of anions in the aqueous mixtures formed via a protonation transfer reaction has been confirmed by the H-1 NMR spectroscopy and UV-vis absorption spectrum of 18DHAQ dye. The study also establishes that the Reichardt's E-T(30) dye can be used as a valid polarity probe to study the solvatochromic behavior of the binary mixtures of amino acid-based ionic liquids.

Kinetic profile and catalytic activity of transition metal-based ionic liquids for reduction of nitroarenes via in situ formation of nanoparticles - Thawarkar, Sachin R.; Khupse, Nageshwar D.; Kumar, Anil (Chemistryselect, 2017)
The experimentally determined apparent rate constant (k(app)) shows that the [BmIm](2)[PdCl4] and [BmIm](2)[NiCl4] act as effective catalysts for the reduction of nitroarenes to aminoarenes in the presence of NaBH4. The TEM, XPS, XRD and dynamic light scattering studies show that there is in situ formation of Pd and Ni metal Nanoparticles (NPs) from the reduction of [BmIm](2)[PdCl4] and [BmIm](2)[NiCl4], respectively which are responsible for the enhancement in the catalytic activity. Thus, in the presence of the ionic liquid stabilized metal NPs show higher catalytic activity in comparison to the NPs stabilized with other capping agents as reported. The order of k(app) as 1) PNP > 2-BrPNP > 2-APNP and 2) PNP > ONP > 2-NR for reduction of nitroarenes using [BmIm](2)[PdCl4] and [BmIm](2)[NiCl4] and its correlation explained on the basis of electronic structure and hydrogen bonding ability of nitroarenes. The thermodynamic parameters such as E-a, Delta H-#, Delta S-# and Delta G(#) are in agreement with the surface catalyzed reduction reaction of PNP in the presence of NPs as catalyst. The kapp values illustrated the reduction reaction follow the LangmuirHinshelwood (L-H) mechanism.

Probing the solute-solvent interactions in the binary mixtures of ionic liquids with water and alcohols by conductance, viscosity and IR spectroscopy - Jain, Preeti; Kumar, Anil (Journal of Molecular Liquids, 2017)
The molar conductance and viscosities of the bisulfate ([HSO4](-)) and ethylsulfate ([EtSO4](-))-based imidazolium ionic liquids in various molecular solvents have been measured at 298.15 K as a function of concentration of ionic liquids (1 x 10(-4) to 0.1 mol L-1). It is shown that the anions have considerable effect on the molar conductance and association constant of the [HSO4](-) and [EtSO4](-)-based imidazolium ionic liquids. Higher molar conductance of the [HSO4](-)-based imidazolium ionic liquids in polar protic solvents (water and methanol) is noted as compared to the [EtSO4](-)-based imidazolium ionic liquids, though the [HSO4](-)-based imidazolium ionic liquids possess higher association constant in water than in methanol. The intermolecular interactions in the pure and binary mixture of [HSO4](-) and [EtSO4](-)-based imidazolium ionic liquids have been investigated by IR spectroscopy. The C-2-H stretching vibration frequency of the imidazolium ring reveals the H-bonding between cations and anions of pure ionic liquids and their solutions. The transport properties (limiting molar conductance, transport number, ionic mobility and diffusion coefficient) of cations and anions correlate well with the hydrodynamic radius in their aqueous solutions. The study shows that the energy barrier for charge transfer is minimal as compared to the fluidity of the aqueous solution of the studied ionic liquids obtained from the Arrhenius equation. (C) 2017 Elsevier B.V. All rights reserved.

Thermodynamic and molecular origin of interfacial rate enhancements and endo-selectivities of a Diels-Alder reaction - Beniwal, Vijay; Kumar, Anil (Physical Chemistry Chemical Physics, 2017)
Organic reactions in general display large rate accelerations when performed under interfacial conditions, such as on water or at ionic liquid interfaces. However, a clear picture of the physicochemical factors responsible for this large rate enhancements is not available. To gain an understanding of the thermodynamic and molecular origin of these large rate enhancements, we performed a Diels-Alder reaction between cyclopentadiene and methyl acrylate at ionic liquid/n-hexane interfaces. This study describes, for the first time, a methodology for the calculation of the activation parameters of an interfacial reaction. It has been seen that the energy of activation for an interfacial reaction is much smaller than that of the corresponding homogeneous reaction, resulting into the large rate acceleration for the interfacial reaction. Furthermore, the study describes the effects of the alkyl chain length of ionic liquid cations, the extent of heterogeneity, and the polarity of ionic liquids on the rate constants and stereoselectivity of the reaction.

Benzoin condensation: a kinetic monitoring at the oil-water interface - Singh, Anshu; Kumar, Anil (ChemistrySelect, 2018)
The overall kinetics of condensation of benzaldehyde to benzoin has been discussed here with an aim to develop a better understanding of the change in reactivity of the interfacial reaction in the presence of co-solvents. A key aspect of the 'on water' reaction is the chemistry between solvent and reactants that occur at the oil-water interface. In particular the orientation of water molecules at the interface plays a key role in catalyzing the reaction. An initial increase in the rate constants of reaction is observed, followed by sharp fall in the reaction kinetics. An interesting interplay of hydrophobicity, hydrogen bonding and polarity of the binary mixture is inevitable in the present study. The observations are nevertheless important reference point for future investigations of 'on water' reactions.

Enthalpic interactions in aqueous strong electrolytes upon addition of ionic liquids - Jain, Preeti; Kumar, Anil (Physical Chemistry Chemical Physics, 2018)
The present study deals with the inter-ionic interactions between strong electrolytes and ionic liquids based on the thermodynamic properties such as excess partial molar enthalpy, H-IL(E), relative apparent molar enthalpy, phi(L), and the enthalpic interaction parameters. The thermodynamic properties of the systems are the key indicators to understand the interionic interactions. We have conducted a systematic investigation of the enthalpic behavior of aqueous solution of salts and ionic liquids and their mixtures. The present study also emphasizes how the H-IL(E) values for the mixture of aqueous solution of ionic liquids and salts deviate from linearity as compared to those of the constituent aqueous ionic liquid or salt. This deviation from linearity for the H-IL(E) values has been discussed here.

Excited state intramolecular proton transfer in 1,8-Dihydroxy-9,10-anthraquinone dye: Revealing microstructures in [C(n)mIm][NTf2] and [C(n)mIm][BF4] series of ionic liquid solvents - Beniwal, Vijay; Kumar, Anil; Pal, Haridas (Journal of Photochemistry and Photobiology A-Chemistry, 2018)
Excited state intramolecular proton transfer (ESIPT) in 18-dihydroxy-9,10-anthraquinone (18DHAQ) dye has been investigated in two series of 1-alkyl-3-methylimidazolium ([C(n)mIm](+)) based ionic liquid (IL) solvents, [C(n)mlm][NTf2] and [C(n)mlm][BF4], with n = 2, 4, 6, 8 and 10, using steady-state (SS) and time resolved (TR) fluorescence studies. In both the IL series, fluorescence intensity for tautomer (T*) form gradually decreases relative to normal (N*) form with increasing n value for [C(n)mlm](+) cations. Observed results suggest microstructure formation and its consequent effect on the ESIPT process of the dye in these IL solvents. Since more extensive microstructures are likely with larger n values of [C(n)mIm](+) cations, the dye is expectedly solubilized more in the polar microdomains of the solvent microstructures, resulting better stabilization for the more dipolar N* state and hence a higher emission intensity from this state. This proposition is clearly supported by ultrafast (sub-picosecond) fluorescence kinetics for both N* and T* states, though sub-nanosecond TR results indicate very similar fluoresce decays for both N* and T*, suggesting an eventual kinetic equilibrium between two states subsequent to the initial ultrafast and fast forward and backward ESIPT processes. Small differences between the results in the [C(n)mIm][NTf2] and [C(n)mIm][BE4] series of ILs are attributed to dissimilar size, shape and basicity of [NTf2]- and [BF4]- anions, responsible for some characteristic changes in the microstructures formed in the respective solvent series. To the best of our knowledge, present study is the only report demonstrating modulations in the ESIPT process through microstructure formations in neat [C(n)mIm](+) based IL solvents. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: 1; 1-Alkyl-3-methylimidazolium ionic liquids; 8-Dihydroxyanthraquinone; Emission modulations of tautomeric forms; ESIPT process; Microstructure formation

Excited-state prototropism of 7-hydroxy-4-methylcoumarin in [C(n)mim][BF4] series of ionic liquid-water mixtures: insights on reverse micelle-like water nanocluster formation - Beniwal, Vijay; Kumar, Anil; Pal, Haridas; Choudhury, Sharmistha Dutta (Photochemical & Photobiological Sciences, 2018)
This study explores the excited state prototropic behavior of the fluorophore, 7-hydroxy-4-methylcoumarin (7H4MC), in the [C(n)mim][BF4] (n = 2, 4, 6, 8, 10) series of ionic liquid (IL)-water mixtures at low water contents. In pure IL media, 7H4MC exists in the neutral form in both ground and excited states. However, on addition of water to the ILs, the excited neutral form of the dye is gradually converted to the anionic and the tautomeric species, leading to characteristic changes in the emission spectra. The similarity in the spectral features of 7H4MC in the IL-water system with that in a conventional reverse micelle system rather than with organic solvent-water mixtures, suggests that in the presence of water, the ILs are organized into reverse micelle-like structures with the consequent formation of confined water pockets. The results further suggest that formation of water nanoclusters and the ensuing changes in excited state prototropic behavior of the dye, is facilitated by increase in the alkyl chain length of the IL cation. These propositions are supported by time-resolved fluorescence studies. To the best of our knowledge this is the first report on proton transfer reaction in IL-water mixtures at low water contents. Considering that ILs are useful as solvents and surfactants, and IL-water mixtures in particular have applications in chemical extractions and biocatalysis, an understanding of the structural organization and water pool formation in these systems is quite important. The insights obtained from the prototropic transformations of 7H4MC are significant not only for fundamental self-assembly studies, but also for the development of ILs as chemical reaction media.

Three-dimensional printing with waste high-density polyethylene - Gudadhe, Aniket; Bachhar, Nirmalya; Kumar, Anil; Andrade, Prem; Kumaraswamy, Guruswamy (ACS Applied Polymer Materials, 2019)
Fused filament fabrication (FFF) three-dimensional (3D) printing of semicrystalline polymers such as high density polyethylene (HDPE) is challenging because crystallization-induced shrinkage of the filament, as it cools, results in stresses that warp the printed part and debond it from the print substrate. Here, we demonstrate that waste-derived HDPE can be successfully 3D printed by (i) blending with a small fraction (<0.5% by weight) of dimethyl dibenzylidene sorbitol (DMDBS) and (similar to 10%) linear low density polyethylene (LLDPE) and (ii) printing the object with a thin ``brim'' around it that is adhered to the print substrate using common polyvinyl acetate-based glue. We match our experimental results with FEM simulations that provide insight into the origin of the stresses developed during printing. Because HDPE forms a significant fraction of the plastic waste stream, conversion of waste-derived HDPE to 3D printing filament has important technological implications.
Keywords: 3d printing polyethylene printing; polymer blend; Recyclability; warpage

Water-assisted stability of carbene: cyclic voltammetric investigation of 1-ethyl-3-methylimidazolium ethylsulfate ionic liquid - Jain, Preeti; Chaudhari, Vijay R.; Kumar, Anil (Physical Chemistry Chemical Physics, 2019)
In this work, we report electrochemical studies on imidazolium-based ionic liquids with an objective to explore the possibility of carbene formation in their dilute aqueous solutions. Conventionally, water plays a detrimental role during investigations involving ionic liquids, and this role has been investigated via electrochemical studies in aqueous ionic liquid solutions. There are varying opinions regarding the influence of water on the physicochemical behaviour of ionic liquids that require an in-depth understanding. To eludicate the role of water, we attempted to evaluate the electrochemical performance of ionic liquids in water as a solvent, and the influence of water on ionic liquids was explored through feasibility and stability studies on carbene formed in an aqueous imidazolium-based ionic liquid solution. The electrochemical investigation of an aqueous solution of 1-ethyl-3-methylimidazolium ethylsulfate ([EMIM][EtSO4]) revealed a redox couple. Detailed investigations suggest that reduction of the imidazolium cation occurs at the C2 position, with subsequent formation of carbene. Furthermore, an anodic peak was found to be associated with the oxidation of carbene. The coulometric process associated with the anodic peaks indicated that the two-electron oxidation of carbene occurred. The stability of carbene in water was evaluated through the use of different protic and aprotic solvents. The hydrogen bond-forming ability of carbene with water seems to be responsible for its improved stability in water.

3D printing of semicrystalline polypropylene: towards eliminating warpage of printed objects - Bachhar, Nirmalya; Gudadhe, Aniket; Kumar, Anil; Andrade, Prem; Kumaraswamy, Guruswamy (Bulletin of Materials Science, 2020)
Fused filament fabrication (FFF) is an extrusion-based 3D printing technique for thermoplastic polymers. In this technique, molten polymer is extruded through a print nozzle and is laid down layer by layer to build up the printed object. Currently, FFF is used primarily to print amorphous or low-crystallinity polymers, such as acrylonitrile butadiene styrene copolymer (ABS) or polylactic acid (PLA). Printing of semicrystalline polymers, such as polyethylene or polypropylene remains particularly challenging. During FFF of semicrystalline polymers, large thermomechanical stresses are generated when the polymer solidifies on cooling. These stresses result in warpage of the printed part. Here, we analyse the factors that influence stresses generated during FFF 3D printing of a commercial semicrystalline polymer, isotactic polypropylene. We investigate the effect of height of the printed object on part warpage, as well the effect of infilling during printing. We demonstrate that the stresses generated during FFF can be substantially decreased by incorporation of a `brim', viz. a thin layer at the base of the printed object, and by adhering the brim to the print substrate using common polyvinyl acetate-based glue. We systematically investigate the effect of the brim size on the warpage of the printed object. We support our experimental findings with finite element method (FEM) simulations that explain the mechanism of stress buildup during printing. The trend in stresses calculated in the FEM simulations parallel the warpage measured in the experiments. Thus, this work represents an important methodological advance towards warpage-free FFF printing of semicrystalline polymers.
Keywords: 3D printing; polypropylene printing; warpage

Binary mixtures of aprotic and protic ionic liquids demonstrate synergistic polarity effect: an unusual observation - Thawarkar, Sachin; Khupse, Nageshwar D.; Kumar, Anil (Journal of Solution Chemistry, 2020)
In this communication, we demonstrate the solute-solvent and solvent-solvent interactions in the binary mixtures of two aprotic ionic liquids, namely 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide and 1-butyl-1-methylpyrrolidinium bis(trifluoromethylsulfonyl)imide, with the protic ionic liquid 1-methylimidazolium acetate. The synergistic effects as expressed by the solvatochromic parameter are noted. This observation is in contrast to the mixing of protic ionic liquids 1-methylpyrrolidium acetate and 4-methylmorpholine acetate with 1-methylimidazolium acetate, respectively. It appears that the synergistic effects in the binary mixtures of aprotic and protic ionic liquids are caused by the formation of hydrogen bonds, since cations are dominant H-bond donors while anions are dominant H-bond acceptors. Preferential solvation models are used to describe the solute-solvent interactions in the binary ionic liquid mixtures.
Keywords: binary mixture; Ionic liquid; polarity; Preferential solvation; synergetic effect